Haematologicaland Biochemicalparameters Of Captive Spotted Deer (Axisaxis) As A Reference Value - R, Seemanthini; Jani , R.G. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Haematological and blood biochemical status were measured in 20 sedated chital deer (Axis axis) (2-8 years of age) reared in different captive environment to compare as reference values vis-à vis domestic small ruminants for assessing their health status. Haemoglobin, haematocrit (PCV), total erythrocyte count and total leucocyte count were measured to show 10.8± 0.87 g/dl, 38.0 ±0.7%, 12.6±0.8×106 and 5.20 ±0.2×103 respectively. The mean corpuscular volume, mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration were found to be 28.6±1.4µ3, 8.2±0.6 µg, and 26.4±1.5% respectively. The erythrocyte size was of microcytic type in spotted deer. Amongst the different leukocyte neutrophil predominated (58.0 ±1.50%) over lymphocyte (40.0 ±1.24 %) compared to other small ruminant species. Plasma glucose, serum total protein, cholesterol and urea concentration were 68.00±8.01 mg/dl, 9.80±0.60g/dl, 134.00 ± 09.20 mg/dl and 24.20 ±0.36 g/dl respectively. Serum calcium and phosphorus showed in normal range stress of handling due to chemical immobilization and restraint may have induced some alteration in these haemato-biochemical parameters which is difficult to be eliminated and similar observation may be compiled for reference in captive deer species.